ANALISIS PENDAPATAN PETANI KARET DAN SISTEM PENGOLAHAN BAHAN OLAH KARET (BOKAR) (Kasus di Desa Tanah Abang Kecamatan Batanghari Leko Kabupaten Musi Banyuasin) (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
This study aims to: (1) Calculated rubber farmers income tenants and owners of tenant farmers in the village of Tanah Abang subdistrict Batang Leko and (2). reviewing the material processing system Olah Rubber (Bokar) processing by the farmers in the village of Tanah Abang subdistrict Batang Leko. The sampling used in this study is the method of stratified random lopsided